English-Chinese Translation as Conquest and Resistance in the Late Qing 1811-1911 A Postcolonial Perspective - Huang, Xiaojia; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book examines how translation facilitated the Western conquest of China and how it was in turn employed by the Chinese as a weapon to resist the invasion in the late Qing 1811-1911. It brings out the question on the role of translation as part of the Western conquest of Late Qing China, with special attention drawn to the deceptions and manipulations in the translation of the Sino-foreign unequal treaties signed during 1840-1911. The readers will benefit from the assertion that translation did not remain innocent, but rather became intermingled with power abuses in the Chinese milieu as well.
1 Introduction -- 2 Translation as Conquest and Resistance: A Historical Overview -- 3 E-C Translation as Conquest in the Late Qing1811-1911 -- 4 E-C Translation as Resistance in the Late Qing1811-1911 -- 5 Conclusions.
Keywords: Anthropological linguistics; Comparative literature; Linguistic Anthropology; Comparative Literature